Lightning distance mobile application lightning distance calculator - Basri, S. (Institute of Electrical and Electronics Engineers Inc., 2016)
Lightning strike can be fatal to any human or can even cause injuries. Since Malaysia is one of the countries with the highest number of lightning strikes in the world, the number of deaths and injuries are quite high due to low level of awareness of lightning safety and its dangers. Moreover the calculation of the lightning distance is been done manually and not so accurate. Calculating the distance between a person and the nearby lightning strike can determine whether an individual is in a safe distance from it. Hence, since most Malaysians nowadays use mobile applications on their smartphones it is an evitable to develop more flexible lightning distance calculation apps. Therefore the objective of this study is to develop a lightning distance calculator mobile application following the RAD methodology. It is consist three main phases of a development cycle iteration which are analysis and design and lastly followed by implementation. Overall the mobile application has the ability to calculate distance between lightning strike and current location and nearby city, store the records online, and mark circles on map to show possible lightning strikes area. Â© 2016 IEEE.